Strategy pemasaran dodol ketan pada era digitalisasi di Kecamatan Bajubang Kabupaten Batang Hari - Ade Jermawinsyah Zebua; Ulyia (Journal of Creative Attitudes Culture, 2026)
This research is entitled "Marketing Strategy for Sticky Rice Dodol in the Digitalization Era in Bajubang District, Batang Hari Regency." This research is motivated by the challenges faced by the Sticky Rice Dodol Business in Muara Bulian District. The purpose of this research is to formulate an appropriate marketing strategy for the digitalization era for the sticky rice dodol business. The method used is descriptive qualitative with SWOT analysis to identify internal factors (strengths and weaknesses) and external factors (opportunities and threats). In conclusion, the implementation of intensive digital marketing can increase sales and competitiveness of the sticky rice dodol business.